Chaotic Dynamics of Colpitts Oscillator Under Control of MEMS Feedback - Mishra, Saumitra; Yadava, R. D. S. (Journal of Applied Nonlinear Dynamics, 2026)
The nonlinear dynamics of Colpitts oscillator under control of MEMS varactor in feedback connectivity has been analyzed with objectives for generation and control of high frequency chaotic signals. The feedback signal derived from the capacitive divider in the standard Colpitts oscillator is modified by the MEMS varactor response mirrored by a voltage-controlled current multiplier. The latter implements MEMS capacitance multiplication and serves as a control parameter. The effects of voltage nonlinearity of the MEMS capacitance and the capacitance multiplication factor (α) have been analyzed by employing Lyapunov exponent, bifurcation diagram, phase portrait and Fourier transform methods. The modified feedback network facilitates high frequency chaos generation due to frequency doubling and high pass filtering effects of the MEMS capacitance. The latter emphasizes high frequency generation and attenuates lower frequencies. The variation of capacitance multiplication factor allows systematic changes in the qualitative nature of oscillator dynamics from a stable low frequency noisy state to Hopf bifurcation to period doubling/ tripling to chaos generation. The analysis suggests new MEMS based tuning and control of chaotic Colpitts oscillations.